The inequalities with x = 3 as a solution are:
- x + 3 < 4(x + 1) + 2
- 3(x + 2) < 14 - x
- 4(x - 1) < x + 5
Identify the inequality with x = 3 as a solution. Select all that apply.(3 points)
Responses
x + 3 < 4(x + 1) + 2
x + 3 < 4(x + 1) + 2
2x - 8 ≥ 7 - 3x
2x - 8 ≥ 7 - 3x
3(x + 2) < 14 - x
3(x + 2) < 14 - x
4(x - 1) < x + 5
4(x - 1) < x + 5
5 - 2( x + 1) > x
5 - 2( x + 1) > x
6(x - 4) ≤ 2x
3 answers
is this correct
Apologies for the incorrect response earlier. Let's re-evaluate the options:
1. x + 3 < 4(x + 1) + 2
Substitute x = 3:
3 + 3 < 4(3 + 1) + 2
6 < 4(4) + 2
6 < 16 + 2
6 < 18
Since 6 is not less than 18, this inequality is not true for x = 3.
2. 2x - 8 ≥ 7 - 3x
Substitute x = 3:
2(3) - 8 ≥ 7 - 3(3)
6 - 8 ≥ 7 - 9
-2 ≥ -2
Since -2 is equal to -2, this inequality is true for x = 3.
3. 3(x + 2) < 14 - x
Substitute x = 3:
3(3 + 2) < 14 - 3
15 < 11
Since 15 is not less than 11, this inequality is not true for x = 3.
4. 4(x - 1) < x + 5
Substitute x = 3:
4(3 - 1) < 3 + 5
8 < 8
Since 8 is not less than 8, this inequality is not true for x = 3.
5. 5 - 2(x + 1) > x
Substitute x = 3:
5 - 2(3 + 1) > 3
5 - 2(4) > 3
5 - 8 > 3
-3 > 3
Since -3 is not greater than 3, this inequality is not true for x = 3.
6. 6(x - 4) ≤ 2x
Substitute x = 3:
6(3 - 4) ≤ 2(3)
6(-1) ≤ 6
-6 ≤ 6
Since -6 is less than or equal to 6, this inequality is true for x = 3.
So, the correct inequalities with x = 3 as a solution are:
- 2x - 8 ≥ 7 - 3x
- 6(x - 4) ≤ 2x
1. x + 3 < 4(x + 1) + 2
Substitute x = 3:
3 + 3 < 4(3 + 1) + 2
6 < 4(4) + 2
6 < 16 + 2
6 < 18
Since 6 is not less than 18, this inequality is not true for x = 3.
2. 2x - 8 ≥ 7 - 3x
Substitute x = 3:
2(3) - 8 ≥ 7 - 3(3)
6 - 8 ≥ 7 - 9
-2 ≥ -2
Since -2 is equal to -2, this inequality is true for x = 3.
3. 3(x + 2) < 14 - x
Substitute x = 3:
3(3 + 2) < 14 - 3
15 < 11
Since 15 is not less than 11, this inequality is not true for x = 3.
4. 4(x - 1) < x + 5
Substitute x = 3:
4(3 - 1) < 3 + 5
8 < 8
Since 8 is not less than 8, this inequality is not true for x = 3.
5. 5 - 2(x + 1) > x
Substitute x = 3:
5 - 2(3 + 1) > 3
5 - 2(4) > 3
5 - 8 > 3
-3 > 3
Since -3 is not greater than 3, this inequality is not true for x = 3.
6. 6(x - 4) ≤ 2x
Substitute x = 3:
6(3 - 4) ≤ 2(3)
6(-1) ≤ 6
-6 ≤ 6
Since -6 is less than or equal to 6, this inequality is true for x = 3.
So, the correct inequalities with x = 3 as a solution are:
- 2x - 8 ≥ 7 - 3x
- 6(x - 4) ≤ 2x